Immobility, precarity and the Covid-19 pandemic: the impact of lockdown on international students in Portugal - Cairns, D. (2021)
This article looks at the impact of the Covid-19 pandemic among international students in Portugal, focusing on their experiences during the Spring 2020 lockdown. The discussion begins with an outline of the research context, and recognition of the inherent precarity of much international student life. Our research questions hence look not only at the immediate impact of the pandemic on internationalised learning but also the heightening of pre-existing economic vulnerability among many of our research subjects. Using evidence taken from 27 interviews, we document their experiences, including the challenge of maintaining communications and coping with social isolation, and look at how the pandemic has undermined the financial integrity of international studentship. In conclusion, we argue that in addition to widespread stress and anxiety the pandemic has created additional forms of precarity for this cohort, creating a need to integrate better support measures into the governance of mobility at tertiary education level.